Environmental Tobacco Smoke in Relation to Bladder Cancer Risk—The Shanghai Bladder Cancer Study - Tao, Li; Xiang, Yong-Bing; Wang, Renwei; Nelson, Heather H.; Gao, Yu-Tang; Chan, Kenneth K.; Yu, Mimi C.; Yuan, Jian-Min (Cancer epidemiology, biomarkers & prevention, 2010)
Background: Environmental tobacco smoke (ETS) contains tobacco carcinogens. Hepatic cytochrome P450 (CYP) 1A2 and N-acetyltransferase (NAT2) are important isoenzymes in activation and detoxification, respectively, of tobacco carcinogens. Data on ETS and bladder cancer risk are sparse. Methods: We examined the effects of ETS alone and combined with NAT2/CYP1A2 on bladder cancer risk among lifelong-nonsmokers in a case-control study involving 195 patients and 261 controls in Shanghai, China. A comprehensive history of ETS exposure was determined through in-person interviews while CYP1A2 and NAT2 phenotypes by a caffeine-based urinary assay. Results: ETS exposure was related to an overall statistically nonsignificant 38% increased bladder cancer risk. The risk increased with increasing number of cigarettes smoked by household members or number of hours per day at workplace where coworkers smoked. Compared with no ETS exposure, subjects living with smoking parents during childhood had an OR of 2.43 (95% CI = 0.99–5.96) for bladder cancer. When all ETS sources were combined, the risk increased with increasing total ETS score (Ptrend = 0.03). The OR for high versus nil ETS exposure was 3.00 (95% CI = 1.24–7.26). The increased risk with ETS was mainly seen among individuals possessing a CYP1A2 high efficiency and/or a NAT2 slow acetylation phenotype (Ptrend = 0.04). Conclusions: ETS was associated with an increased bladder cancer risk for lifelong-nonsmokers. The association was stronger for people possessing the at-risk phenotypes of CYP1A2 and/or NAT2. Impact: Reducing exposure to ETS for children and genetically more susceptible individuals could be more effective for bladder cancer prevention. Cancer Epidemiol Biomarkers Prev; 19(12); 3087–95. ©2010 AACR.